Surgical outcome of congenital valvar aortic stenosis - Elshershari, Huda; Alehan, Dursun; Demircin, Metin; Paşaoğlu, İlhan and Bilgiç, Arman (The Turkish Journal of Pediatrics, 2002)
Valvar aortic stenosis is a common congenital heart defect for which surgical procedures can be done with low risk except in infants whose conditions are seriously compromised. The purpose of this report was to present our experience with the results of surgical aortic valvotomy for congenital valvar aortic stenosis performed at our hospital. The study group consisted of 24 patients, 3 females and 21 males, with ages ranging from 1 to 15.5 years (mean age 8.5 years), who underwent aortic valvotomy for valvar aortic stenosis. The case records of all the patients were retrospectively reviewed. They were followed for 1-10.5 years (mean 5.02±2.38 years) after relief of aortic stenosis, and were scheduled for reevaluation. Sixteen of the 24 patients were recatheterized and 15 (93.7%) were found to have aortic regurgitation on angiography. Peak systolic pressure gradients (mean±SD) were 65.9±19.5 mmHg before and 36.7±14.8 mmHg (p<0.05) after the operation. Of the 24 patients, 45.8% had a new postoperative diastolic murmur. Twenty patients (83.3%) had residual stenosis and three (12.5%) had recurrent stenosis. Two patients (8.3%) had undergone reoperation six to seven years after the initial aortic valvotomy, and most of the others will require reoperation in the future. No sudden deaths occurred in this series. Timely relief of obstruction prevents sudden death and produces symptomatic improvement in valvar aortic stenosis, but aortic valvotomy is only a palliative measure.